Revised lectotypification of the name Calendula maritima (Asteraceae) - Troia, Angelo; Greuter, Werner; Raimondo, Francesco Maria (Phytotaxa, 2012)
Calendula maritima Gussone (1825: 3) is endemic to a few coastal areas near Trapani, western Sicily, Italy. Its taxonomic distinctness is generally recognised, even though some authors have treated it as a subspecies rather than species, either as C. incana subsp. maritima (Guss.) Ohle (1974: 279) or as C. suffruticosa subsp. maritima (Guss.) Meikle (1976: 274), its uncertain position reflecting the difficulty in establishing a satisfactory taxonomic classification within the highly diverse genus Calendula Linnaeus (1753: 921). Calendula maritima has recently been included in an IUCN pilot project devoted to the study of the fifty most threatened Mediterranean island plants (Montmollin & Strahm 2005) and, in that context, it has been made the central subject of a special international meeting (Troia & Raimondo 2011).